The Analytical Metaphysics of Time and the Recent Theory of History: Overtones of the Debate about Presentism - Cardoso Jr., Hélio Rebello (História da Historiografia: International Journal of Theory and History of Historiography, 2021)
The longstanding line of research that the analytic tradition calls metaphysics of time remains quite ignored by the theory of history. To bring them closer, this study proposes to introduce to historians and theorists of history the metaphysics of time theses about the presentism/eternalism and the linear/closed time. For such purpose, we drew correspondences between the theory of history and the analytical metaphysics of time concerning some characteristics of the emerging concepts of historical time. These characteristics are related to the recent debate about presentism regarding the regimes of the historical time (multiple temporalities and pluritemporality); plural time in the analytical metaphysics and synchronous/asynchronous historical time; linear/closed time in the analytic tradition and being affected by historical time. As a result, this article presents how the analytical metaphysics of time theses disclose unnoticed contours related to the history theorists’ understanding about the relation with the past.